Analisis Keefektifan Pembelajaran Online di Masa Pandemi Covid-19 - Briliannur Dwi C; Aisyah Ameli; Uswatun Hasanah; Hidayatur Rahman; Abdy Mahesha Putra (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to obtain information about the effectiveness of the online learning process in the Covid-19 pandemic. The study uses explorative qualitative methods with an inductive approach. In this study, the respondents involved were 5 people from SD Banyuajuh 6 Kamal, consisting of 2 teachers, 2 student guardians, and 1 student. To maintain the confidentiality of respondents' identities, researchers gave the names of respondents P1, P2, P3, P4, and P5. The interviews were conducted in a structured manner with questions compiled and linked and developed with related literature. The results of this study are less effective online learning because of the lack of facilities and infrastructure as well as the unpreparedness of technological education.